The effect of types of initial drive-in steps on technical factors in basketball - Park, S.; Yoon, S. (Korean Journal of Sport Biomechanics, 2018)
Objective: The purpose of this study was to investigate the effect of types of drive-in initial steps in basketball on technical factors, to provide basic information for the enhancement of basketball skill. Method: Ten men (age: 24.70±2.26 years; height: 181.00±5.72 cm; weight: 75.70±8.23 kg; career length: 10.00±3.59 years), each with a career length of over five years and no history of injury to the lower extremities within the prior six months, participated in this study. They were asked to perform four types of drive-in movements at 35~60°, wearing their own shoes, after running from a start line 5 m away and catching a basketball passed by an expert passer. The drive-in movements were measured by eight infrared cameras (Oqus 300, Qualisys, Sweden). Collected raw data were used to calculate total initial step time, displacement, velocity, center of mass (COM) height, and COM velocity. Results: Total initial step displacement and velocity of cross drive-ins (JC, SC) were greater than that of direct drive-ins (JD, SD; p < .05). COM velocity of cross drive-ins (JC, SC) was also greater than that of direct drive-ins (JD, SD; p < .05). Conclusion: Our results indicated that cross drive-ins, regardless of stop step type, are more effective than direct drive-ins. This is because cross drive-ins are technically bold due to less influence from walking violations and double dribble rules in basketball. However, using one-sided movement is too difficult to play in competitive game; therefore, basketball players should develop the ability to choose appropriate movement frequency.